Organizational Experience as Formation of Competitive Student’ Character - Sabrina; Adda, Harnida Wahyuni; Bakri Hasanuddin; Mohammad Ega Nugraha (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
This study aims to explore the role of organizational experience in the formation of competitive student character in the higher education environment. The literature study research method was used to summarize key findings that support the positive influence of organizational participation on student character development. The results of this study indicate that student organizations have a considerable role in shaping character values through student activities provided in higher education. Organizational experience contributes to the improvement of leadership and teamwork skills, shaping the character of student who are adaptive and ready to contribute in a professional environment. Due to the role of ormawa in the campus towards the formation of student character, student can later have knowledge and experience in organizing, as well as character building which can later become the hallmark of student.